Comparison of Civil Legal Responsibility in BPJS Health Services in Indonesia and National Health Service in England - Helma Widya; Angga Aldilla Gussman (JURNAL AKTA, 2026)
This study examines and compares civil legal liability in the provision of health services between the Social Security Administration for Health (BPJS Kesehatan) in Indonesia and the National Health Service (NHS) in the United Kingdom. Both health insurance systems represent concrete forms of state intervention in fulfilling citizens' basic rights to health, but have fundamentally different legal foundations, institutional structures, and civil legal liability mechanisms. Using a normative-comparative legal research method, this study analyzes the legal construction of civil liability, dispute resolution mechanisms, and legal protection for participants in both systems. The results show that Indonesia still relies on a liability approach based on the Civil Code (KUHPerdata) and sectoral regulations with high institutional fragmentation, while the United Kingdom has established an integrated NHS Resolution system with a mature negligence doctrine and an efficient compensation mechanism. This study recommends structural reforms to the BPJS Kesehatan civil legal liability system towards a more integrated, transparent, and participant-protection-oriented model.